2012
DOI: 10.1016/j.oceaneng.2012.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Regular and irregular wave impacts on floating body

Abstract: a b s t r a c tFully nonlinear wave-body interactions for a stationary floating structure under regular and irregular waves for different water depths, wave heights and periods are studied in a 2-D numerical wave tank. The tank model is based on Reynolds-averaged Navier-Stokes equations and renormalization group k-e model. The equations are discretized based on the finite volume method. The pressure implicit splitting of operators scheme is employed to treat the pressure-velocity coupling and a compressive int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, this method is based on the linear wave theory, hence will be limited within small wave steepness conditions. The computational fluid dynamic (CFD) method, which solves fully nonlinear Navier-Stokes equations covering the effect of viscous and turbulence, has been frequently used for hydrodynamic performance prediction in wave and floating body interaction process, and shows great potential in nonlinear effect prediction [21,22]. Wei et al studied the viscous effect and slamming process on bottom hinged oscillating wave energy converters based on the CFD software ANSYS Fluent, and revealed that CFD results agree well with experiments in capturing local features of the flow as well as dynamics of the device [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, this method is based on the linear wave theory, hence will be limited within small wave steepness conditions. The computational fluid dynamic (CFD) method, which solves fully nonlinear Navier-Stokes equations covering the effect of viscous and turbulence, has been frequently used for hydrodynamic performance prediction in wave and floating body interaction process, and shows great potential in nonlinear effect prediction [21,22]. Wei et al studied the viscous effect and slamming process on bottom hinged oscillating wave energy converters based on the CFD software ANSYS Fluent, and revealed that CFD results agree well with experiments in capturing local features of the flow as well as dynamics of the device [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the potential flow theory is not valid and other tools based on Computational Fluid Dynamics (CFD) solvers to resolve the full Navier-Stokes equations or Lattice Boltzmann method (LBM) have been used [35][36][37][38][39][40]. Most of these problems have been formulated in 2D, and despite the increase of computational power, the full 3D models require a considerable computational cost.…”
Section: Introductionmentioning
confidence: 99%
“…The different modes of body motion were more specifically studied in a recent paper by Zhou et al (2013). For completeness, numerical models based on the full Navier-Stokes equations were also proposed in 2D (Rahman et al (2006);Hadžić et al (2005); Ghasemi et al (2014)) and, in particular, wave impact on structures in regular and irregular waves was also investigated in Li and Lin (2012). But the accurate direct solution of Navier-Stokes equations for non-linear wave-structure interaction problems, particularly in 3D, still remains a computationally formidable task that poses greater numerical difficulties than when using potential flow theory.…”
Section: Introductionmentioning
confidence: 99%